GREEN AGENDA AS A NEW PARADIGM OF AGRICULTURE IN BOSNIA AND HERZEGOVINA (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
By signing the Sofia Declaration on the Green Agenda for the Western Balkans, the leaders of the countries, including Bosnia and Herzegovina (BiH), committed themselves to the implementation of five basic courses of action established by the action plan, which include: 1) decarbonization, 2) circular economy, 3) depollution, 4) sustainable agriculture and 5) protection of nature and biodiversity. This commitment means that the creation and implementation of policies should be strongly marked by an environmental approach, not only because of EU requirements but also because of the practical importance for overall sustainable development. Because of this, support measures in an increasing number of countries imply the application of measures such as making direct payments subject to the fulfillment of the so-called cross-compliance or special payments for agroecological practices, sustainable land management, etc. However, the measures included in the Green Agenda in BiH are applied very modestly, which will be presented in this paper for the period 2018-2021. Practically, measures to support organic production, soil fertility control, and the protection of genetic resources are the only ones on track with the Green Deal goals. It is expected that the new strategic documents in the field of agriculture will take into account the objectives of the CAP, and thus the Green Deal, and will bring the agriculture policy of BiH closer to the policy of the EU, for which BiH decided a long time ago.